Differentially abundant proteins, metabolites, and lipid molecules in spaghetti meat compared to normal chicken breast meat: Multiomics analysis - Janghan Choi; Majid Shakeri; Brian Bowker; Hong Zhuang; Byungwhi Kong (Poultry Science)
Spaghetti meat (SM), a recently emerging muscle myopathy in chicken breast meat, is characterized by a loss of muscle fiber integrity, resulting in a spaghetti-like appearance. Understanding the differences in proteins, metabolites, and lipids through a multiomics approach in SM can identify its quality traits and elucidate its exact causes. The purpose of this study was to investigate differentially abundant proteins, metabolites, and lipid molecules in SM compared to normal chicken breast meat (Control). The supernatant from sample homogenates was subjected to ultra-high performance liquid chromatography (UHPLC) analysis for multiomic profiling. A total of 16 chicken breast fillets (Pectoralis major) representing Control (n = 8) and SM (n = 8) groups were collected from a commercial slaughterhouse. A total of 2593 molecules were identified and composed of 1903 proteins, 506 lipids, 181 compounds and 3 electrolytes. There were 632 differential molecules composed of 503 proteins, 76 lipids, 50 metabolites, and 3 electrolytes. In comparing SM and Control, the protein, metabolite, and lipid molecules with the greatest fold change were calponin, decanoylcarnitine, and ceramide [N‑hydroxy-sphingosine] (Cer[NS]) d18:1_26:1, respectively. Plasmenylphosphatidylcholine (Plasmenyl-PC) and triglycerides (TG) were significantly decreased and increased, respectively, in SM compared to Control. Acylcarnitines (AC) were significantly decreased in SM compared to Control. Decanoylcarnitine, lauroylcarnitine, linoleyl-carnitine, oleoyl-carnitine, hexanoylcarnitine were downregulated in SM compared to Control, and adenosine 5′-diphosphoribose and nicotinamide adenine dinucleotide (NAD) were downregulated in SM. Carbon metabolism, glycolysis/glucogenesis, ribosome, biosynthesis of amino acids, and aminoacyl-tRNA biosynthesis were selected in the top 10 enriched Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, identified by using differential proteins. Hence, SM had different proteins, metabolites, and lipid molecules related to β-oxidation, carbon and energy metabolism, lipid formation, and protein and amino acid metabolism compared to Control. Results from this study showed physiological alterations found in SM myopathy. Therefore, to mitigate SM in broilers, interventions should: 1) increase NAD and carnitines, 2) reduce triglycerides, and 3) modulate β-oxidation and energy metabolism via nutritional, genetic, or systemic approaches.